Non-Verifiable Emissions, Voluntary Agreements, and Emission Taxes - Karine Nyborg (Statistics Norway, Research Department, 1998)
This paper demonstrates that voluntary agreements between a regulator and an industry can be Pareto superior to environmental taxes. Further, such agreements may differ from direct regulation in a non-trivial way. The first-best optimum may be included in the set of possible agreements, even if it is not attainable using tax instruments. There is no uncertainty or asymmetric information in the model. However, it is assumed that some emissions are observable, but not verifiable. This may be interpreted as a situation where precise formal specification of the pollutant is infeasible.
Keywords: H21; L52; Q28; 330; Voluntary agreements; Second-best tax; Non-verifiability